Method for preparing lactic acid through hemicellulose heterogeneous catalysis
By using mesoporous silica support solid-supported lanthanum trifluoropotassium sulfonate as a heterogeneous catalyst during the lactic acid preparation process, hemicellulose is efficiently converted into lactic acid, which solves the problems of low lactic acid preparation efficiency and difficult catalyst recovery in the prior art, and achieves high yield and low cost lactic acid production.
Patent Information
- Application Number
- CN202411525211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-25
AI Technical Summary
The existing lactic acid preparation methods have long cycles, low production efficiency, and difficult catalysts to be recycled, which limits the large-scale production and application of lactic acid.
Mesoporous silica is used as a support to solid-support lanthanum trifluoropotassium trifluorosulfonate and as a heterogeneous catalyst. Hemicellulose is converted into lactic acid through high-temperature hydrothermal conditions to achieve efficient recycling of the catalyst.
It improves the yield of lactic acid, realizes stable solid load and recycling of catalysts, reduces production costs, and has great industrial application prospects.
Smart Images

Figure BDA0005109043270000071 
Figure HDA0005109043280000011 
Figure HDA0005109043280000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lactic acid preparation, and in particular to a method for preparing lactic acid from hemicellulose by using a heterogeneous catalyst. Background Art
[0002] Lactic acid is one of the three major organic acids in the world. It can be used as an intermediate for the production of propylene glycol, propylene oxide and polylactic acid, and is widely used in the fields of chemical industry, food, and pharmaceuticals. The traditional preparation method of lactic acid is generally produced by fermentation of monosaccharides (e.g., glucose, xylose, etc.), which has a long cycle and low production efficiency. In addition, the difficulty of lactic acid bacteria cultivation technology limits the large-scale production and application of lactic acid. The current demand for lactic acid is huge, but the production cost is high. Producing lactic acid using biomass raw materials is an effective way.
[0003] Lignocellulose is composed of cellulose, hemicellulose, and lignin. It is not only abundant in reserves and low in cost, but also easy to obtain. Hemicellulose accounts for 15% to 30% of lignocellulose. It has a low molecular weight and an amorphous structure. It can be hydrolyzed into monosaccharides and then converted into high value-added products such as lactic acid. In practical applications, the preparation of lactic acid by hemicellulose catalysis faces challenges in many aspects, such as catalyst selection, reaction condition optimization, catalyst stability and recycling benefits, and environmental impact.
[0004] In view of this, there is an urgent need to develop a heterogeneous catalyst with excellent performance and high catalytic activity to achieve efficient conversion of hemicellulose to produce lactic acid. Summary of the invention
[0005] The purpose of the present invention is to develop a heterogeneous catalyst with excellent performance and high catalytic activity to achieve efficient conversion of hemicellulose to produce lactic acid, improve the lactic acid yield and realize the recycling of the heterogeneous catalyst.
[0006] The present application provides a method for preparing lactic acid by catalyzing hemicellulose with a heterogeneous catalyst, comprising the following steps:
[0007] S1: dissolve P123 in deionized water and stir until homogeneous at room temperature; after P123 is completely dissolved, obtain a P123 solution; add HCl solution to the P123 solution and stir for 4 hours at 25°C until homogeneous; obtain solution A for standby use;
[0008] P123 is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer;
[0009] S2: Slowly add ethyl orthosilicate to solution A in S1, and vigorously stir at 40°C to obtain a mixed solution B; the stirring temperature is 40°C; the stirring time is 2h;
[0010] S3: The mixed solution B in S2 is transferred to a polytetrafluoroethylene hydrothermal autoclave, and cooled after crystallization, and then filtered and dried; a white powder is obtained; the crystallization temperature is 100° C.; the crystallization time is 48 h;
[0011] S4: calcining the white powder obtained in S3 for the first time to obtain mesoporous silica;
[0012] S5: Dissolve lanthanum trifluoropotassium sulfonate in ethanol, then add the mesoporous silica in S4 and mix thoroughly, react at 105°C and dry, calcine the dried powder for the second time at 350°C in air, and collect to obtain a heterogeneous catalyst; the second calcination time is 5h;
[0013] S6: Hemicellulose, catalyst and deionized water are fully mixed and then loaded into a high-pressure reactor; the high-pressure reactor is sealed and the air in the reactor is replaced with an inert gas; the catalytic conversion reaction is started under the set temperature and stirring speed conditions, and the reaction is maintained at a constant temperature when the set temperature is reached. After the reaction is completed, the heating is stopped, the reactor is taken out and cooled to room temperature, the pressure is released, and the reaction liquid is collected.
[0014] Furthermore, the concentration of the P123 solution in S1 is 1-150 g / L, and the concentration of HCl is 2 mol / L.
[0015] Furthermore, the mass ratio of P123 to HCl solution was 1:30.
[0016] Furthermore, the mass ratio of P123 to tetraethyl orthosilicate is 4:9.
[0017] Furthermore, the temperature of the first calcination in S4 is 550° C. and the time is 5 h.
[0018] Furthermore, the material-liquid ratio of lanthanum trifluoro potassium sulfonate to mesoporous silica in S5 is (1.2:1)-(5:1) (mmol:g).
[0019] Furthermore, the reaction time in S5 is 2 to 48 hours.
[0020] Furthermore, the mass ratio of hemicellulose to the catalyst is (1:1) to (4:1).
[0021] Furthermore, in S6, the temperature is set to 190-250° C., the stirring speed is set to 300 r / min, and the constant temperature reaction time is set to 1 h.
[0022] Furthermore, the reaction temperature in S5 is 105° C. and the reaction time is 24 h.
[0023] Beneficial Effects
[0024] 1. The present invention uses mesoporous silica as a carrier to successfully immobilize lanthanum trifluoro potassium sulfonate, which not only retains the high catalytic activity of the homogeneous catalyst but also realizes the efficient circulation of the catalyst. The large specific surface area and uniform pore size distribution of the mesoporous silica carrier provide more active sites for the catalyst, thereby improving the dispersibility and accessibility of the catalyst, and further improving the catalytic efficiency. As a catalyst, lanthanum trifluoro potassium sulfonate has a unique chemical property that can effectively promote the saccharification of biomass and the synthesis of lactic acid, which is of great significance for improving the production efficiency of lactic acid and reducing production costs.
[0025] 2. The present invention applies a supported catalyst to the process of catalyzing hemicellulose to prepare lactic acid, providing a theoretical basis for the efficient conversion of the sugar components of biomass into lactic acid. The method of the present invention achieves stable immobilization of the catalyst by optimizing the preparation process of the catalyst, reduces the loss of the catalyst during the reaction, and thus improves the service life and economy of the catalyst. Since the catalyst can be recycled, the present invention reduces the demand for fresh catalyst and reduces the catalytic cost.
[0026] 3. The lactic acid preparation process described in the present invention achieves a lactic acid yield of more than 49%. The process has great potential and application prospects in industrial production and can produce a higher yield of lactic acid at a lower cost to meet market demand.
[0027] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The above and other objects, features and advantages of the present application will become more apparent through a more detailed description of exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0029] Figure 1 is a scanning electron microscope image of the immobilized catalyst of the present invention;
[0030] Figure 2 This is a diagram of the lactic acid product of the present invention;
[0031] Figure 3 This is a graph showing the effect of different reaction temperatures on the preparation of lactic acid in Example 1. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0033] The preparation of lactic acid from lignocellulose by chemical catalysis is a method of converting lignocellulose into lactic acid under certain conditions using homogeneous or heterogeneous chemical catalysts. Compared with microbial fermentation, chemical catalysis has the advantages of simple operation, short duration, low cost and high product concentration. Compared with homogeneous catalysts, heterogeneous catalysts are less corrosive, easy to separate from the product, and can be used repeatedly, so they have broader prospects in practical applications.
[0034] The strength of Lewis acid sites is the key to the catalytic preparation of lactic acid. 3+ It is a metal ion with strong Lewis acid sites. Studies have shown that water-resistant lanthanide potassium trifluorosulfonate Ln(OTf)3 can efficiently catalyze the conversion of sugars into lactic acid. - ) has a strong electron-withdrawing ability, which can further improve the Lewis acidity of Ln(OTf)3 and thus realize the rapid conversion of hemicellulose into lactic acid. However, homogeneous catalysts have the disadvantage of being difficult to recycle, and immobilizing them to prepare heterogeneous catalysts is a promising solution. Mesoporous silica has the advantages of large specific surface area, porosity and large pore size, and is an ideal catalyst carrier. The abundant silanol (Si-OH) on the surface of the pore wall of mesoporous silica can realize the uniform surface grafting of lanthanum trifluorosulfonate to prepare an ordered catalyst with uniform pore size, which not only retains the high active sites of the catalyst, but also improves the stability and recyclability of the catalyst.
[0035] Under high temperature hydrothermal conditions, H3O + It can bind to the glycosidic bonds of hemicellulose, thereby hydrolyzing hemicellulose into oligosaccharides. In the presence of La(OTf)3, oligosaccharides are further hydrolyzed into monosaccharides. Based on the proton transfer mechanism, monosaccharides will be hydrolyzed into oligosaccharides in the presence of La(OTf)3. 3+Aldol isomerization occurs under the action of the catalyst. The Lewis acid center in the catalyst will coordinate with the C=O in the sugar molecule and the -OH on its adjacent carbon, and simultaneously attack the α and β carbon atoms on the sugar to break the CC bond, thereby completing the reverse aldol condensation reaction to generate dihydroxyacetone and glyceraldehyde, which are further dehydrated and converted into methylglyoxal, and finally rearranged to generate lactic acid. Ha et al. used Er(OTF)3 as a catalyst to catalyze the preparation of lactic acid from coffee grounds under certain conditions. The purity of the lactic acid product was not high and the catalyst was difficult to recover (Journal of Environmental Chemical Engineering, 2023, 11(5): 110682). Wang Shiwei immobilized ytterbium trifluorosulfonate on the MCM-41 carrier for the catalytic preparation of lactic acid from glucose. The maximum lactic acid yield was only 16.41%. The carrier had a small pore size, and the loading process caused the pore size to be blocked, resulting in a reduction in active sites (China University of Mining and Technology (Beijing), 2019, 39-49).
[0036] Example 1
[0037] (1) Dissolve 4.0 g of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) in 30 mL of deionized water and stir at room temperature for 4 h until homogeneous; after P123 is completely dissolved, add 120 g of 2 mol / L HCl and stir thoroughly at 40 ° C for 2 h. Slowly add 9 g of TEOS to the above solution under vigorous stirring and continue stirring at 40 ° C for 20 h. Transfer the obtained mixed solution to a polytetrafluoroethylene hydrothermal reactor, crystallize in an oven at 100 ° C for 48 h, filter and dry after cooling, and then calcine the obtained white powder in a muffle furnace at 550 ° C for 5 h to obtain mesoporous silica SBA-15.
[0038] (2) 0.5 mmol of lanthanum trifluoropotassium sulfonate was dissolved in 3 mL of ethanol, mixed thoroughly with 0.1 g of mesoporous silica at room temperature for 30 min, reacted and dried at 105 °C for 24 h, and the dried powder was calcined for a second time at 350 °C in air for 5 h to obtain a heterogeneous catalyst.
[0039] (3) Dissolve 100 mg of hemicellulose completely in 30 mL of deionized water and load it into an autoclave, then disperse 25 mg of the catalyst in the above hemicellulose solution. Seal the autoclave and purge it with nitrogen (inert gas) for 3-5 minutes to replace the air in the autoclave. Start the catalytic conversion reaction at a set temperature of 230°C and a stirring speed of 300 r / min, and maintain a constant temperature reaction for 1 hour when the set temperature is reached. After the reaction is completed, stop heating, take out the autoclave and cool it to room temperature, release the pressure, and collect the reaction liquid. Detect in a liquid chromatograph to obtain the yield of each product. The same below.
[0040] Lactic acid yield (%) = (amount of lactic acid substance / amount of hemicellulose substance) × 100%
[0041] Example 2
[0042] Implement steps (1) and (2) according to the steps of Example 1, set the set temperature in step (3) to 250°C, and continue to implement the steps of Example 1.
[0043] Example 3
[0044] The steps (1) and (2) were carried out according to the steps of Example 1, the amount of catalyst in step (3) was set to 50 mg, and the steps of Example 2 were continued.
[0045] Example 4
[0046] The steps (1) and (2) were carried out according to the steps of Example 1, the amount of catalyst in step (3) was set to 75 mg, and the steps of Example 2 were continued.
[0047] Example 5
[0048] Step (1) and step (3) were carried out according to the steps of Example 2, 0.17 mmol of lanthanum trifluoro potassium sulfonate in step (2) was dissolved in 3 mL of ethanol, and the steps of Example 2 were continued.
[0049] Comparative Example 1
[0050] (1) Dissolve 4.0 g of P123 in 30 mL of deionized water and stir at room temperature for 4 h until homogeneous; after P123 is completely dissolved, add 120 g of 2 mol / L HCl and stir thoroughly at 40 °C for 2 h. Slowly add 9 g of TEOS to the above solution under vigorous stirring and continue stirring at 40 °C for 20 h. Transfer the resulting mixed solution to a polytetrafluoroethylene hydrothermal reactor and crystallize in a 100 °C oven for 48 h. After cooling, filter and dry, and then calcine the resulting white powder in a muffle furnace at 550 °C for 5 h to obtain mesoporous silica SBA-15.
[0051] (2) 0.5 mmol of lanthanum trifluoropotassium sulfonate was dissolved in 3 mL of ethanol, and mixed with 0.1 g of mesoporous silica at room temperature for 30 min, reacted at 105° C. and dried for 24 h. The dried powder was calcined at 350° C. in air for 5 h, and the heterogeneous catalyst was collected.
[0052] (3) 100 mg of hemicellulose was completely dissolved in 30 mL of deionized water and loaded into a high-pressure reactor. The high-pressure reactor was sealed and purged with nitrogen for 3-5 minutes to replace the air in the reactor. The catalytic conversion reaction was started at a set temperature of 250°C and a stirring speed of 300 r / min. When the set temperature was reached, the reaction was kept at a constant temperature for 1 hour. After the reaction was completed, the heating was stopped, the reactor was taken out and cooled to room temperature, the pressure was released, and the reaction liquid was collected. The yield of each product was obtained by detection in a liquid chromatograph.
[0053] Example sample test:
[0054] The concentration of lactic acid was measured by high performance liquid chromatography. The ratio of the amount of lactic acid to the amount of hemicellulose was calculated to obtain the yield of lactic acid. The results are as follows:
[0055] Table 1 Lactic acid yield of each example
[0056]
[0057] According to the data in Table 1, the reaction temperature of Example 1 is relatively high, and the lactic acid yield is relatively good. In Example 5, the loading amount of the catalyst is reduced, and the lactic acid yield decreases, indicating that low loading amount is not conducive to the production of lactic acid. In Example 2, the temperature of the reaction system is increased, and the lactic acid yield increases with the increase of temperature, indicating that high temperature conditions are necessary conditions for achieving high lactic acid yields. Under high temperature conditions, the occurrence of the reverse aldol reaction is favorable, so that more hemicellulose is converted into lactic acid. Compared with the preparation of lactic acid by biological fermentation, the lactic acid preparation time is significantly shortened. From the perspective of technical economy, it has good prospects in the preparation of lactic acid. In Example 3, the lactic acid yield is relatively high, and the addition of the catalyst promotes the occurrence of the reaction. In Example 4, the lactic acid yield is close to 50%, and the increase in the amount of catalyst promotes the active sites in the reaction system, so the yield increases. In Comparative Example 1, no catalyst is added to the reaction system, and the lactic acid yield is extremely low, indicating that the catalyst has a significant effect on the preparation of lactic acid.
[0058] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing lactic acid by catalyzing hemicellulose with a heterogeneous catalyst, characterized in that: The steps include: S1: dissolving P123 in deionized water, stirring at room temperature until homogeneous; after the P123 is completely dissolved, a P123 solution is obtained; adding HCl solution to the P123 solution, stirring at 25±1°C for 4h until uniform; obtaining solution A for standby use; The P123 is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer; S2: Slowly add tetraethyl orthosilicate to the solution A in S1 while stirring to obtain a mixed solution B; the stirring temperature is 40° C. and the stirring time is 2 h; S3: transferring the mixed solution B in S2 to a polytetrafluoroethylene hydrothermal autoclave, cooling it after crystallization, and then filtering and drying it; obtaining a white powder; the crystallization temperature is 100° C.; the crystallization time is 48 hours; S4: calcining the white powder obtained in S3 for the first time to obtain mesoporous silica; S5: dissolving lanthanum trifluoropotassium sulfonate in ethanol, then adding the mesoporous silica in S4 and mixing them thoroughly, reacting and drying at a temperature of 60 to 105° C., calcining the dried powder for a second time at 350° C. in air, and collecting to obtain a heterogeneous catalyst; the second calcination time is 5 hours; S6: Hemicellulose, catalyst and deionized water are fully mixed and then loaded into a high-pressure reactor; the high-pressure reactor is sealed and the air in the reactor is replaced with an inert gas; the catalytic conversion reaction is started under the set temperature and stirring speed conditions, and the reaction is maintained at a constant temperature when the set temperature is reached. After the reaction is completed, the heating is stopped, the reactor is taken out and cooled to room temperature, the pressure is released, and the reaction liquid is collected.
2. The method according to claim 1, characterized in that: The concentration of the P123 solution in the S1 is 1-150 g / L, and the concentration of HCl is 2 mol / L.
3. The method according to claim 1, characterized in that: The mass ratio of the P123 to the HCl solution is 1:
30.
4. The method according to claim 1, characterized in that: The mass ratio of P123 to tetraethyl orthosilicate is 4:
9.
5. The method according to claim 1, characterized in that: The temperature of the first calcination in S4 is 550° C. and the time is 5 h.
6. The method according to claim 1, characterized in that: The material-liquid ratio of lanthanum trifluoro potassium sulfonate to mesoporous silica in S5 is (1.2:1)-(5:1) (mmol:g).
7. The method according to claim 1, characterized in that: The reaction time in S5 is 2 to 48 hours.
8. The method according to claim 1, characterized in that: The mass ratio of hemicellulose to catalyst is (1:1) to (4:1).
9. The method according to claim 1, characterized in that: In the step S6, the temperature is set at 190-250° C., the stirring speed is 300 r / min, and the constant temperature reaction time is 1 h.
10. The method according to claim 1 or 7, characterized in that: The reaction temperature in S5 is 105° C. and the reaction time is 24 h.